Relationship between facets of lifestyle and subjective happiness among undergraduates in Universiti Putra Malaysia (UPM) - Chek, Kin Keuw; Ahmad, Sa'odah (2015)
This study aims to determine the relationships between facets of lifestyle (physical health and exercise, psychological health, substance use, nutrition, environmental concern, social concern, accident prevention or safety and sense of purpose) and subjective happiness of UPM’s undergraduates. A sample of 400 undergraduates were chosen as respondents in this study. The results showed that all the variables of facets of lifestyle were significantly related to undergraduates’ subjective happiness. The findings revealed that undergraduates with higher score in facets of lifestyle have a higher score in subjective happiness. The implication is that the more positive and healthy the lifestyle, the happier a person will be.